Investment climate in Ukraine and the ways of its improvement - Yandyuk, Alexey (My University, 2014)
Favourable investment climate is an important factor in attracting investments to build a structured economy, introduce innovative products, accrue reserves of enterprises, improve the living standards of people and encourage rapid economic growth of the country. When making investment decisions, foreign investors primarily take into account the investment climate in the country. Therefore nowadays, the improvement of investment climate is the most important challenge for Ukraine, and it determines the actuality of this problem. Сприятливий інвестиційний клімат є важливим фактором у залученні інвестицій в будівництво структурованої економіки, впровадження інноваційних продуктів, запаси підприємств, підвищення рівня життя людей і сприяє швидкому економічному зростанню країни. При прийнятті інвестиційних рішень, іноземні інвестори в першу чергу враховувати інвестиційний клімат в країні. Тому в даний час, поліпшення інвестиційного клімату найбільш важливим завданням для України, і це визначає актуальність цієї проблеми.
Keywords: investment climate; economy; investments; інвестиційний клімат; економіка; інвестиції